Design and implementation of the participatory German network for translational dementia care research (TaNDem): A mixed‐method study on the perspectives of healthcare providers and dementia researchers in dementia care research - Annelie Scharf; Anika Rädke; Daniel Purwins; Marie Marleen Heppner; Stefanie Köhler; Martina Roes; Stefan Teipel; Wolfgang Hoffmann; Bernhard Michalowsky (Wiley, 2023)
Abstract Background Currently, there is a lack of interaction between research and healthcare practice. As a result, research findings reach healthcare practice only late, and topics relevant to practice are often not known in research. Involving people living with dementia (PlwD), their relatives and healthcare providers in dementia care research can accelerate this process. For inclusion, firm and reliable structures are needed, which are to be established with the help of the Translational Network for Dementia Care Research in Germany. However, there is only limited knowledge about the priorities, expectations and conditions of stakeholders (healthcare providers and dementia researchers) for such cooperation within a network. Objectives The aim is to gather stakeholders' views on (i) future research topics to be addressed within the dementia care research network, (ii) the nature of collaboration within the network and (iii) the facilitating and hindering factors for establishing such a network. Methods Within an exploratory sequential mixed‐method study, we interviewed 87 stakeholders within eleven semistructured focus group interviews. The interviews were transcribed, pseudonymized and analyzed using qualitative content analysis. The qualitative data were analyzed with MAXQDA. Based on the qualitative results found in the focus group interviews, a supplementary online questionnaire was developed to prioritise and rank these findings afterwards. Results Stakeholders prioritized a comprehensible transfer of research results into practice, increased involvement of PlwD and their relatives (additionally marginalized groups such as people with a migrant background) in research and exchange between researchers. Cooperation should preferably occur in a regional context with local contacts, and the latest research results should be made available via an online database. The stakeholders' time, finances and human resources should be considered. Conclusion Stakeholders have partly similar preferences and goals for cooperation and involvement, emphasizing that such interaction in a network offers the possibility of long‐term, effective collaboration and added value for practice and research. Patient or Public Contribution For this study, dementia healthcare providers and dementia care researchers were asked about their perspectives. Their involvement is further elucidated in the manuscript text.